Hypoxia-Inducible Factors Regulate Osteoclasts in Health and Disease - Meng, Xianyi; Wielockx, Ben; Rauner, Martina; Bozec, Aline (Frontiers in Cell and Developmental Biology, 2021)
Hypoxia-inducible factors (HIFs) have become key transcriptional regulators of metabolism, angiogenesis, erythropoiesis, proliferation, inflammation and metastases. HIFs are tightly regulated by the tissue microenvironment. Under the influence of the hypoxic milieu, HIF proteins allow the tissue to adapt its response. This is especially critical for bone, as it constitutes a highly hypoxic environment. As such, bone structure and turnover are strongly influenced by the modulation of oxygen availability and HIFs. Both, bone forming osteoblasts and bone resorbing osteoclasts are targeted by HIFs and modulators of oxygen tension. Experimental and clinical data have delineated the importance of HIF responses in different osteoclast-mediated pathologies. This review will focus on the influence of HIF expression on the regulation of osteoclasts in homeostasis as well as during inflammatory and malignant bone diseases.